Requirements engineering toward sustainable world : third Asia-Pacific Symposium, APRES 2016, Nagoya, Japan, November 10-12, 2016, Proceedings /: third Asia-Pacific Symposium, APRES 2016, Nagoya, Japan, November 10-12, 2016, Proceedings. (2016) - Unknown
No abstract available